Last flight out ebook - Guggenheim, Marc (Last Flight Out., 2022)
With less than twenty-four hours before the last ark leaves a dying Earth, Dr. Ben Caewood's daughter Sara has gone missing. Finally, the critically acclaimed series about a father and daughter trying to reconcile at the end of the world is collected into a single, unforgettable graphic novel from Marc Guggenheim (Arrow, X-Men) and Eduardo Ferigato (Radiant Black). Collects the six-issue miniseries. ""Fans of Ad Astra and Arrival will definitely want to give this series a read."" –But Why Tho? ""Last Flight Out contains all the action of a summer blockbuster and a message that is timely without being preachy. Backed by solid artwork, this is one flight you won't want to miss!"" –Kaboooom